KERAGAAN PERTUMBUHAN DAN HASIL BEBERAPA GENOTIPE TOMAT (Solanum lycopersicum - Qulub Muwafakoh; Deviona Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Tomato plants are shrubs and are classified as annual plants. Tomato plants have oval-shaped leaves, the edges of the leaves are serrated and have pinnate slits that curve inward. The hairy leaves are about 20-30 cm long and 15-20 cm wide with a stalk length of about 3-6 cm. The research was conducted at the Technical Implementation Unit of the Experimental Gardens, Faculty of Agriculture, Riau University, Jl. BinaWidya Km 12.5 SimpangBaru, Tampan, Pekanbaru City. This study lasted for 6 months, starting from July to December 2020. This study was a randomized block design experiment (RAK) consisting of 6 treatments and 3 groups, 18 experimental units were obtained. Each experimental unit contained 20 plants. The data observed in the form of quantitative data. The parameters that will be observed are as follows: Flowering age, Harvest age, the ripe fruit, Plant height, Stem diameter, andThe number of fruit cavities. Observation of the number of cavities was carried out as many as 10 pieces per bed. The 7 genotypes tomatoes produced different performances from one genotype to another, especially in plant height, fruit length, fruit diameter, and number of fruit cavities. The genotype was found to be better than the Tora IPB variety, namely the genotype SG15- F10 07897D -9-2-1-6-1-8-5-3 which had better plant height, fruit diameter and number of fruit cavities.Keywords : Horticultura, Growth performance, Genotype